Optimal Allocation of Protection and Control Devices in Distribution Networks with Microgrids - Reiz, Cleberton [UNESP]; Lima, Tayenne Dias De [UNESP]; Leite, Jonatas Boas [UNESP]; Javadi, Mohammad Sadegh; Gouveia, Clara Sofia (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Protection and control systems represent an essential part of distribution networks, ensuring the physical integrity of components and improving system reliability. Protection devices isolate a portion of the network affected by a fault, while control devices reduce the number of de-energized loads by transferring loads to neighboring feeders. The integration of distributed generation has the potential to improve the continuity of energy services through islanding operation during outage conditions. In this context, this paper presents a multi-objective optimization approach for the size and allocation of protection and control devices in distribution networks with microgrids supplied by renewable energy sources. Reclosers, fuses, remote-controlled switches, and directional relays are considered in the formulation. The demand and generation uncertainties define the islanding operation and the load transfer possibilities. A genetic algorithm is presented to solve the allocation problem. The compromise programming is performed to choose the best solution from the Pareto front. Results show interesting setups for the protection system and viability of islanding operation.
Keywords: compromise programming; Distribution systems; genetic algorithm; microgrids; Protection system planning